2022
DOI: 10.3390/jrfm15030136
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Senior Executives Characteristics on Corporate Environmental Disclosures: A Bibliometric Analysis

Abstract: This study aims to synthesize the literature on the top management team (TMT) characteristics influence on environmental disclosures of public organizations and identify recent trends, key themes, influential journals, and authors. Our study recruited 88 research articles on the relationship of TMT characteristics and environmental disclosures from 54 academic journals published from 2010 to 2021 for bibliometric analysis. Our study has identified three influential streams: (1) Role of Politically connections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 96 publications
0
15
0
Order By: Relevance
“…Various study topics have been identified to deepen understanding of the research outcomes. These existing themes can be strategically categorized and visualized through a graph to evaluate the significance and evolution of each research theme [ 68 ]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Various study topics have been identified to deepen understanding of the research outcomes. These existing themes can be strategically categorized and visualized through a graph to evaluate the significance and evolution of each research theme [ 68 ]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This relationship is significant at a 1% level of significance in all the 10 models presented in Table 3 , which explains that firms with low leverage ratios have extra money for spending on CSR, as confirmed by some other researchers such as Mishra and Modi ( 2013 ). The main reason for this negative relationship is that firms spending on CSR are more ethical in its hierarchy of top management teams and also in boards of directors (Arslan et al 2022a , b , c ; Li et al 2016a , b ), resultantly firms perform better financially and have less requirements for debt to fulfill capital requirements (Harjoto 2017 ; Mishra and Modi 2013 ; Sheikh 2019 ; Swandari and Sadikin 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…The second objective of the study is to contribute to the identification of core journals, articles, authors, keywords, and other aspects of the field using Biblioshiny and Microsoft Excel. Specifically, for influential sources and core authors we use H-Index, total citations (TC), and annual net publications (NP) to identify them (Arslan et al, 2022). In addition, Bradford's law is used to tri-categorize major journals.…”
Section: Scheme Of Studymentioning
confidence: 99%